PENINGKATAN KETERAMPILAN SISWA MENULISKAN KATA MELALUI PENGGUNAAN MEDIA FLASHCARD (Penelitian Pre-Eksperimen pada Pembelajaran Bahasa Inggris di Kelas III SDN Cieunteung 3 Kota Tasikmalaya) - FAUZIAH, Rida Nurul (2014)
This research is about improving student's skill in writing word through of using media flashcard. This research based on background by media which using by teacher for drilling the student in English learning is not varied. Using media flashcard has opportunity for implemented in English writing learning in elementary school. Media flashcard has benefits for improving student's skill in writing word. With that case demands of English writing learning in 3rd grade is not optimal yet, so media flashcard opportunity to used it. Through the pre-experimental which used in SDN Cieunteung 3 is expected to obtain empirical evidence. The purpose of this research is to obtain the empirical evidence about the enhancement student's skill in writing word by using media flashcard in English learning in 3rd grade SDN Cieunteung 3 Kota Tasikmalaya. In this research used quantitative of method, while the data gotten through test technique. The data source in this research is student of 3rd grade in SDN Cieunteung 3 Kota Tasikmalaya. Based on result of hypothesis experiment was point our average of gain score > 0, and average of N-Gain score > 0,3 then Ha accepted and Ho ignored. Thus it can be seen that N-Gain > 0,3 with the score 0,44 > 0,3. These result indicated that there is an enhancement students' write the word skill by using the media flashcard in writing the English word learning (Ha is accepted). Keyword: Media, Flashcard, student's skill, writing word